Digital-to-analog converter - Hsieh Wen-Hung; Hung Chung-Chih (My University, 2012)
The present invention relates to a digital-to-analog converter comprising a differentiation circuit, a conversion circuit, and an integration circuit. The differentiation circuit receives and differentiates a digital signal for producing a differentiation signal. The conversion circuit is coupled to the differentiation circuit. It receives the differentiation signal and produces a conversion signal according to a clock signal and the differentiation signal. The integration circuit is coupled to the conversion circuit. It receives and integrates the conversion signal for producing an analog signal. Thereby, the purpose of reducing distortion noises can be achieved.